Prueba de Estreptococo Beta Hemolítico del Grupo “B” (Agalactiae) en embarazadas de 35- 37 semanas del Centro Médico Loja Salud - Ocampo Córdova, Ana Gabriela (2020)
Group B Streptococcus Beta or Streptococcus Agalactiae (GBS), is a gram-positive bacterium which is part of the flora of the female genital tract, during the pregnancy it can be present and cause serious infections in the newborn. In Ecuador, the prevalence is around 11-13% of patients with positive results. For this reason, the objective of this research is to know the prevalence of the Group B Streptococcus Beta test (Agalactiae) in 35-37 week pregnant women from the “Loja Salud” Medical Center, period 2016-2018. This study was descriptive, retrospective, cross sectional with a quantitative approach. All women aged between 18 and 35 years old were selected who turned up to the “Loja Salud” Medical Center, with a sample of 147 patients, who 40 women underwent the Beta Hemolytic Streptococcal test (vagina-rectal) the following results were obtained: 97% (n = 39) of negative cases and 3% (n= 1) of positive cases. It was evident that the most frequent age group are between 18 and 23 years old representing a 55% (n= 22), followed by women between 24 and 29 years old who represent 32,5% (n= 13) and only 12,5% (n= 5) of women between 30 and 35 years old who undergo the test. The therapeutic measures that were indicated were in base of an antibiotic sensibility that was performed which was 100% to the penicillin and cefazolin. These results make evident the presence of GBS which results in a worldwide and national problem. Studies at regional level are necessary to establish the prevalence of the bacterium at time and at this manner prevent infections in newborn. Key words: Streptococcus Agalactiae (GBS), vaginal-rectal culture, neonatal sepsis, vaginal delivery.